241 EFFECTIVENESS OF PREOPERATIVE CHEMOEMBOLIZATION FOR HEPATOCELLULAR CARCINOMA IN LIVER TRANSPLANT CANDIDATES PRE- AND POST MODEL FOR END-STAGE LIVER DISEASE. Issue 1 (1st January 2007) - Taghavi, C. E.; Meehan, M.; Colquhoun, S. D.
Abstract : Purpose: To evaluate the impact of hepatic artery chemoembolization (HACE) at our center before and after the implementation of the MELD organ allocation system. Methods: A single-center retrospective review of transplant candidates with HCC treated with HACE. Primary end points included transplantation versus progression beyond transplant criteria/death. Secondary end points included incidence of HACE-related complications and survival. Parameters studied included clinical stage at the time of HACE, findings of imaging and explant pathology, as well as the interval from HACE to a primary end point. Patients were categorized according to the transplant listing date relative to February 27, 2002, as pre-MELD and post-MELD era. Statistical comparisons were made using a two-tailed t -test and survival was determined using the Kaplan-Meier method ( GraphPad Prism ® v4.0c). Results: Of 26 pre-MELD era patients, 19 (73%) were transplanted (mean wait = 357.2 days), with 1-, 3-, and 5-year survivability of 73%, 55%, and 44%, respectively. Seven (27%) were removed from the waiting list due to increased tumor burden or death at a mean time of 185.3 days, with 1- and 3- year survivability of 17% ( p = .0096). Of the 35 post-MELD era patients, 17 (48%) were transplanted (mean = 161.7 days) with 1- and 3-year survivability of 87%. Nine (26%) were removed from the list (mean wait = 218.4 days) with a 1-year survivability of 0% ( p = .0032). Nine (26%) patients remain listed in stable condition (mean = 332 days). No serious HACE-related complications were reported in either group, and survival was excellent (100%). Conclusions: HACE was associated with significant tumor necrosis in both pre- and post-MELD era patients, as evidenced by imaging and pathology. This study shows that although pre- and post-MELD era patients experienced almost identical progression of disease precluding transplantation, post-MELD patients had improved survivability following transplantation. Given the efficacy of HACE, this therapy continues to have a positive impact on pretransplant candidates.